Temporary Salt Lakes: Ecosystem Services Shift in a Ramsar Site Over a 50-Year Period - Ioannidou, Ioanna; Manolaki, Paraskevi; Litskas, Vassilis D.; Vogiatzakis, Ioannis N. (Frontiers in Ecology and Evolution, 2021)
Changes in land use/ land cover (LULC) are the key factors driving biodiversity and ecosystem services decline globally. This study examines spatiotemporal LULC changes in a Ramsar coastal temporary wetland (Larnaca Salt Lake) on the island of Cyprus between 1963 and 2015. LULC changes in the area are related to variations in the provision of ecosystem services (ES) namely food provision, climate regulation, avifauna support and landscape aesthetics. LULC mapping was performed based on the interpretation of aerial photos taken in 1963, while 2015 mapping was based on CORINE classification validated by satellite image analysis and fieldwork. We used the following indicators for the ES examined: 1) crops’ yield for the estimation of food supply, 2) carbon storage potential for climate regulation, 3) land cover potential to support avifauna richness and 4) naturalness as a proxy for landscape aesthetics. Quantifications were based on a mixed-methods approach with the use of statistical data, expert opinion and bibliography. Estimates for every service were assigned to CORINE land use classes (CLC) present in the area. Landscape structure was measured using a suite of commonly employed landscape metrics. The results showed that between 1963 and 2015 there has been a significant reduction in food provisioning service by 75%, a 37% reduction in carbon storage capacity, an 11% reduction in the capacity to support avifauna, and a 13% reduction in landscape aesthetics. Increased soil surface sealing, mainly with the placement of the international airport, which resulted in the conversion of natural or semi-natural to artificial surfaces, has been the main reason for the decrease in ES supply over the last fifty years in the study area. The character of the area in terms of land use types richness and diversity remains fairly stable but the dominant land use types have experienced fragmentation. The study sets the basis for a monitoring scheme to evaluate the state of the temporary wetlands with emphasis placed on spatial processes as a link to ES provision.